Pengaruh Financial Distress, Capital Intensity, Pertumbuhan Penjualan dan Kepemilikan Manajerial terhadap Penghindaran Pajak: (Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023) - Nur Salsa Bella; Suryani Suryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the influence of financial distress, capital intensity, sales growth and managerial ownership on tax avoidance. The population in this study is Property and real estate companies listed on the Indonesia Stock Exchange in the financial statements for the 2020-2023 period. The sampling technique in this study uses the purposive sampling method and obtained as many as 128 sample data from 32 companies. The analysis tool used is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS) Program Version 22.0. The results of this study show that financial distress and capital intensity have a significant positive effect on tax avoidance, while sales growth and managerial ownership do not have a significant effect on tax avoidance.